2019
DOI: 10.1155/2019/9750526
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Behavior and Microstructure of Al-7Si Alloys with Individual and Combined Additions of Sr and Yb

Abstract: The effects of individual and combined additions of Sr and Yb on the solidification behavior and microstructure of Al-7Si alloys were investigated using thermal analysis, optical microscopy, and scanning electron microscopy. The results showed that the nucleation temperature, minimum temperature, and growth temperature of eutectic solidification were lower than those of the unmodified alloys, and eutectic recalescence at 2°C in the Yb- and (Sr + Yb)-modified alloys was observed. The decrease in the nucleation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, they had an obvious refining effect on primary α-Al and needle-like β-phase Fe. Dong et al [22] investigated the effects of Sr and Yb on the refinement of eutectic Si in Al-7% Si alloys, revealing that 0.03 wt% Sr and 0.6 wt% Yb transformed the morphology of eutectic Si from a plate-like form to a fine fibrous structure. Wu et al [23] found that Sr and Ce modification could not only modify and refine Al-Si alloys but also enhance the modification capability of Sr According to literature reports, Y can decrease the size of α-Al dendrite grains [24], and change Si phase from acicular to short rod-shaped [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they had an obvious refining effect on primary α-Al and needle-like β-phase Fe. Dong et al [22] investigated the effects of Sr and Yb on the refinement of eutectic Si in Al-7% Si alloys, revealing that 0.03 wt% Sr and 0.6 wt% Yb transformed the morphology of eutectic Si from a plate-like form to a fine fibrous structure. Wu et al [23] found that Sr and Ce modification could not only modify and refine Al-Si alloys but also enhance the modification capability of Sr According to literature reports, Y can decrease the size of α-Al dendrite grains [24], and change Si phase from acicular to short rod-shaped [25].…”
Section: Introductionmentioning
confidence: 99%